The impact of reaching the anaerobic threshold on some kinematic variables related to the accuracy of shooting the penalty kick among footballers - Alkhawaldeh, Ibtehal M (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to identify the correlation of the kinematic variables in the accuracy of shooting the penalty kick among footballers before and after reaching the anaerobic threshold, and also to identify the impact of reaching the anaerobic threshold on some kinematic variables related to the accuracy of shooting the penalty kick among football players. We used the experimental approach using the divided goal to determine the accuracy extent of shooting the penalty kick in addition to Cunningham and Faulkner Anaerobic Treadmill Test. The study sample consisted of 12 football players from the Jordanian Professional Football League for the year 2021, who are specialized in performing penalty kicks in their clubs. Their average age was 25.1± 4.1 years, average weight 71±2.2 kg and average foot weight 10.9±1.6. The study used Canon Eos 80D cameras, lactate Scout Cortex device and Kinovea 0.8.15 software to analyze the performance. The data was processed through the Statistical Package for the Social Sciences (SPSS). Our study showed that there is a statistically significant relationship at α = 0.05 of the kinematic variables before and after the player reaches the anaerobic threshold with the accuracy of shooting the penalty kick. The results also revealed that there is a statistically significant negative impact at α = 0.05 for reaching the anaerobic threshold on some kinematic variables related to the accuracy of shooting the penalty kick among football players. In conclusion, the kinematic variables of the study and the accuracy of shooting the penalty kick were negatively affected by reaching the anaerobic threshold at a level that exceeds 4.2 mmol/L.